Numbers of Taiga Bean Geese Anseer f. fabalis utilizing the western and central flyways through Sweden during springtime 2007–2015 - Skyllberg, Ulf (Ornis Svecica, 2015)
Bean Geese Anser fabalis were counted at all known spring staging sites in south-central Sweden within the time window when geese migrating along the western and central flyways had left their wintering grounds in Denmark and southernmost Sweden, but before they had crossed the Bothnian Bay to Finland. Reliable counts were obtained for seven years 2007–2015: 57,000 in 2007, 55,500 in 2008, 49,300 in 2009, 46,900 in 2011, 47,400 in 2012, 53,900 in 2014, and 60,200 in 2015. The increase between 2011 and 2015 was significant and may be related to recently decreased hunting pressure in Finland. Subtraction of an estimated 4,000 Tundra Bean Geese Anser f. rossicus and addition of two small populations of Taiga Bean Geese Anser f. fabalis wintering in the UK and in NW Jutland that were likely missed in the counts, yielded a total estimate of 44,200–57,500 Taiga Bean Geese utilizing the western and central flyways. Based on these counts, combined with data on geese wintering east of the Baltic Sea, I estimate the world population to 68,000 Taiga Bean Geese in 2015.